Playback of 50-kHz ultrasonic vocalizations overcomes psychomotor deficits induced by sub-chronic haloperidol treatment in rats - Melo-Thomas, Liana (Psychopharmacology (Berl), 2020)
RATIONALE: In rodents, acute haloperidol treatment induces psychomotor impairments known as catalepsy, which models akinesia in humans and is characterized as an animal model of acute Parkinsonism, whereas sub-chronic haloperidol reduces exploratory behavior, which resembles bradykinesia. Haloperidol-induced catalepsy in rats can be ameliorated by playback of 50-kHz ultrasonic vocalizations (USV), an emotionally and motivationally relevant appetitive auditory stimulus, representing an animal model of paradoxical kinesia. In a condition like PD where patients suffer from chronic motor impairments, it is paramount to assess the long-term symptom relief in an animal model of Parkinsonism. OBJECTIVES: We investigated whether 50-kHz USV playback ameliorates psychomotor deficits induced by haloperidol in a sub-chronic dosing regimen. METHODS: In phase 1, distance traveled and number of rearing behavior were assessed in an activity chamber in order to investigate whether sub-chronic haloperidol treatment induced psychomotor impairments. In phase 2, we investigated whether 50-kHz USV playback could overcome these impairments by assessing exploratory behaviors and approach behavior towards the sound source in the 50-kHz USV radial maze playback paradigm. RESULTS: Sub-chronic haloperidol treatment led to psychomotor deficits since the distance traveled and number of rearing behavior were reduced as compared to saline control group or baseline. These psychomotor impairments were ameliorated during playback of 50-kHz USV, with haloperidol treated rats showing a clear social approach behavior towards the sound source exclusively during playback. CONCLUSIONS: This study provides evidence that 50-kHz USV playback induces paradoxical kinesia in rats exhibiting motor deficits after sub-chronic haloperidol, as we previously showed after acute haloperidol treatment.